Effect of laser power density on formation of oxide particles during ablation of metallic bismuth in atmospheric air - Savelyev, Egor S.; Golubovskaya, Aleksandra G.; Goncharova, Darya A.; Kharlamova, Tamara S.; Svetlichnyi, Valerii A. (Optics and Laser Technology)
Purposeful synthesis of bismuth oxide nanoparticles (NPs) of various crystal modifications is important for biomedicine, photocatalysis and other applications. In this work, pulsed laser ablation of a metallic Bi target in atmospheric air is used to obtain β-Bi2O3 NPs. The effect of the Nd:YAG laser radiation power density (1064 nm, 7 ns) in the range of 0.1-1.2 GW/cm2 on the features of formation of NPs under nonequilibrium conditions is studied, for which the spectra of laser-induced plasma are recorded and analyzed, the plasma composition is determined, and the temperature of the plasma plume is estimated. The NPs are comprehensively characterized using TEM, XRD, FTIR, Raman, and UV-Vis spectroscopies, and electrophoretic light scattering, which make it possible to determine their morphology, crystal structure, chemical composition, and optical properties. The photocatalytic activity of the resulting nanopowders in the Rhodamine B dye decomposition reaction is assessed.